Penggunaan Media Gambar Untuk Meningkatkan Ketrampilan Menulis Karangan Deskripsi Pada Siswa Kelas VII SMP Negeri 2 Petarukan - Khusnul Khotimah; Evi Rosliana (Cakrawala: Jurnal Pendidikan, 2017)
The purpose of this study was to describe the ability to write essay description of the group taught using image media and the group taught without using image media to the students of class VII SMP Negeri 2 Petarukan Pemalang, to describe differences in the ability of the group taught using image media and the group taught without using image media in class VII SMP Negeri 2 Petarukan Pemalang, and to describe the effectiveness of the use of image media in teaching essay writing descriptions in class VII SMP Negeri 2 Petarukan Pemalang. The sampling technique in this research was done by simple random sampling technique. The sample in this research was class VII A as a control group and class VII B as the experimental group. Data collection techniques used was a test. Data was analyzed using t-test non-independent and independent t test. The results showed that there were differences between the description of the essay writing skills taught using image media group and groups that taught without using image media. Results t-value experimental group was 22.06 and the results of t-value control group was 13,81. The experimental group t-value was higher than the control group. The use of image media in teaching essay writing descriptions more effective than without the use of image media. This was proved from the results of the independent t test calculations t-value 5.27> 2.00 t-table. Based on the research results suggests to students to increase interest and ability to write, because writing is one of the four language skills that need to be learned and mastered. Teachers should be more innovative and creative in making or selecting appropriate learning media in order to attract the attention of students in learning activities, so that student achievement will increase